Assessment of a shortened informed consent form for pediatric research: a pilot study. (October 2018) - Murray, Peter; Bierer, Barbara; Hirschfeld, Steven; Klein, Andreas; Davis, Jonathan
Abstract Background Inherent to clinical research is the informed consent process, with the informed consent form (ICF), a key component of human participant protections. We wished to examine whether a shortened and simplified ICF, accompanied by an appendix, improved participant understanding of a study compared with a conventional ICF. Methods A shortened ICF was developed from an existing conventional ICF for a neonatal study. Either the shortened or conventional ICF was randomly distributed to members of two parental advocacy groups. Participants answered survey questions about the form they received. Results Thirty-one out of forty-one (76%) parents in the shortened ICF and 28/41 (68%) in the conventional ICF group responded. Significantly more parents in the shortened ICF group found their form "short and to the point". Although they also stated that the shortened ICF did not provide enough information, there were no significant differences between groups measuring the understanding of key study components. Conclusion A shortened ICF did not impact the understanding of the clinical trial. It will be important to compare the shortened and conventional forms in actual clinical trials.